Characterization and DNA barcoding of Zambian plant species used as inoculum in the traditional fermentation of Munkoyo; a cereal-based beverage - Mubonda Kalumbilo; David Chuba; Agripina Banda; Eddy J. Smid; Sijmen E. Schoustra; Gerlinde B. De Deyn (BMC Plant Biology)
Abstract Background Munkoyo, a non-alcoholic fermented beverage, is traditionally prepared in Zambia and neighbouring countries using cooked grains and the uncooked roots of wild plant species, collectively called ‘Munkoyo’ plants. The drink, valued for its refreshing taste and nutritional contribution, is made using roots of several wild plant species resulting in variations in the taste and quality of the beverage. However, comprehensive information on the specific plant species used in different regions of Zambia, as well as their occurrence in terms of habitat and soil type, is missing. This gap limits our understanding of the factors contributing to Munkoyo’s heterogeneity. The present study sought to identify the Zambian plant species used as an inoculum in Munkoyo fermentation and to characterize the soil in which they occur. Results Plant and soil samples were collected from four districts in Zambia known for Munkoyo production. Using morphological taxonomy, three Fabaceae species were identified as commonly used Munkoyo plants: Rhynchosia insignis (O.Hoffm.) R.E.Fr., Rhynchosia heterophylla Hauman, and Eminia holubii (Hemsl.) Taub. Root colour differed among these species, with the Rhynchosia species having yellowish roots and E. holubii having whitish roots. To validate their identification, we evaluated three DNA barcoding markers (matK, rbcL, and ITS2) for species discrimination. All markers showed 100% PCR amplification and sequencing success rates, with ITS2 displaying the highest genetic variability and species-level resolution. Phylogenetic analyses further confirmed ITS2 as the most effective marker. Validation using samples from a fifth district reaffirmed ITS2’s suitability for species-level discrimination. Soil analysis revealed significant associations between soil texture and plant occurrence: R. insignis and E. holubii were prevalent in sandy soils, while R. heterophylla was more prevalent in soils with lower sand content. Conclusions This study identified three common Munkoyo plant species and demonstrated ITS2 as a robust DNA barcode for their identification. It also established the influence of soil texture on the distribution of these plants, contributing to the understanding of Munkoyo production’s biological and environmental determinants.